Noun Phrase And Its Translation Found In The Novel “The Wonderful Wizard Of OZ” - I Made Juliarta (International Journal of Linguistics and Discourse Analytics, 2022)
This study aimed to: (i) identify the types of noun phrase and its constituent structure found in the story entitled “The Wonderful Wizard of Oz”, (ii) analyze the types of translation shifts of noun phrase in the translation process from English into Indonesian. The Wonderful Wizard of Oz is a modern fairy tale with a distinctly American setting. It has fantasy characters, and data of noun phrases including their translations were found in the novel. In analyzing the translations of noun phrases from English into Indonesian, this study applied shift translation. This study used the theory of translation shift. Translation shifts are the changes occured when there is text translated into another language due to difference between source language and target language. Translation shift theory was proposed by Catford (1978) and the theory of tree diagram that was proposed by Quirk et al. (1985). Qualitative method was applied by the researcher to analyze the data. This study focused on the analysis of noun phrases including tree diagram and its translation. The researcher found that Shifts in translation occurred in the English noun phrases that are also translated into noun phrases in Indonesian as the target language. The study found that unit shift and structure were the translation method used in the translation process from English into Indonesian